Vocational Training of Unemployed Citizens: Experience of the European Union countries - O. S. Sokolov (Ученые записки Российской академии предпринимательства, 2023)
Vocational training programs are an effective way to combat unemployment, especially for people with low levels of education. An active employment policy in this direction can help reduce the skills mismatch that often leads to long–term unemployment among people with low education. The effectiveness of these programs depends on the quality of the training provided, the length of the program, and the types of training. A study of foreign experience has shown that programs that provide both theoretical and on–the–job training tend to be particularly effective in improving employment outcomes.